Self-determination theory and individuals’ intention to participate in donation crowdfunding - Allah Pitchay, Anwar; Aboue Eliz, Noha Mamdouh; Ganesan, Yuvaraj; Mydin, Al-Amin; Ratnasari, Ririn Tri; Mohd Thas Thaker, Mohamed Asmy (Emerald Group Holdings Ltd., 2022)
Abstract Purpose – This study aims to examine the factors that affect individuals’ intention of participating in donation crowdfunding in the context of Oman. Design/methodology/approach – This study used the self-determination theory. A total of 250 respondents from Oman participated. The data is collected by online survey and analyses by using the partial least squares technique. Findings – The results illustrate that sense of self-worth, perceived donor effectiveness and moral obligation positively affect donation intention (DI) towards crowdfunding projects. Furthermore, subjective norms and perceived behavioural control positively impact individuals’ intention to contribute to donation crowdfunding. Originality/value – The results contribute to the literature on donation crowdfunding by identifying the driving forces of individuals’ DI to crowdfunding projects in Oman. Keywords Donation,Crowdfunding,Self-determinationtheory(SDT) Paper type Research paper